FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Priyono, Achmad Agus (Fakultas Ekonomi, UIN Maliki Malang, 2011)
The aim of this study is to examine the causality relationship between structures of assets, firm size, operating leverage, profitability, liquidity, growth of sales, and capital structure. Testing manufactures listed in Indonesian stock market resulted in the estimation structural equation model which is fit and acceptable. Multiple R-square of 0.259 indicate that the change in capital structure is defined by structure of assets (SA), Growth of sales (GS), operating leverage (OL), firm size (FS), liquidity (LQ) and profitability (PR) of 25.9%; while the remaining 74.1% is defined by changes of other variables which were not included in the model.